2020
DOI: 10.3389/fneur.2020.00189
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Combination Strategy to Improve Morphological and Functional Recovery in Rats With Chronic Spinal Cord Injury

Abstract: Immunization with neural derived peptides (INDP), as well as scar removal (SR) and the use of matrices with bone marrow-mesenchymal stem cells (MSCs), have been studied separately and proven to induce a functional and morphological improvement after spinal cord injury (SCI). Herein, we evaluated the therapeutic effects of INDP combined with SR and a fibrin glue matrix (FGM) with MSCs (FGM-MSCs), on motor recovery, axonal regeneration-associated molecules and cytokine expression, axonal regeneration (catecholam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…87 The results showed that the combined therapy was able to modify the non-permissive microenvironment post-SCI but wasn't capable of inducing a proper axonal regeneration or neurogenesis as it was observed after treatment with CNS-related peptides alone. 87 However, they recently observed that combined therapy of monocyte locomotion inhibitor factor, A91 peptide, and glutathione monoethyl ester (GSH-MEE) preserved spinal cord tissue integrity and promoted functional motor recovery in rats following chronicstage SCI. 88 Also, it was reported that the vaccination with spinal cord homogenate-pulsed dendritic cells 89,90 and in particular with A91pulsed dendritic cells 91 enhanced the expression level of BDNF and NT-3 and exerted neuroprotective effect in a SCI mice model.…”
Section: A91mentioning
confidence: 97%
See 2 more Smart Citations
“…87 The results showed that the combined therapy was able to modify the non-permissive microenvironment post-SCI but wasn't capable of inducing a proper axonal regeneration or neurogenesis as it was observed after treatment with CNS-related peptides alone. 87 However, they recently observed that combined therapy of monocyte locomotion inhibitor factor, A91 peptide, and glutathione monoethyl ester (GSH-MEE) preserved spinal cord tissue integrity and promoted functional motor recovery in rats following chronicstage SCI. 88 Also, it was reported that the vaccination with spinal cord homogenate-pulsed dendritic cells 89,90 and in particular with A91pulsed dendritic cells 91 enhanced the expression level of BDNF and NT-3 and exerted neuroprotective effect in a SCI mice model.…”
Section: A91mentioning
confidence: 97%
“…Afterward, the authors designed a combined therapy integrating surgical glial scar removal, a fibrin glue matrix with mesenchymal stem cells, and CNS‐derived peptides 87 . The results showed that the combined therapy was able to modify the non‐permissive microenvironment post‐SCI but wasn't capable of inducing a proper axonal regeneration or neurogenesis as it was observed after treatment with CNS‐related peptides alone 87 .…”
Section: Harnessing “P​a” For Neuro‐regeneration and Cns Injury Recovery With Cns‐related Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Secreted anti-inflammatory cytokines, such as IL-4, IL-10, and TGF-β, are capable of modulating the inflammatory response, resulting in a decrease in the production of several pro-inflammatory factors such as IL-1β, TNF-α and IL-6, by microglia/macrophages ( 143 , 157 , 158 ). Moreover, these cytokines also reduce infiltration of immunocytes, such as macrophages, neutrophils, and monocytes, into inflammatory lesions in the spinal cord by downregulating chemokines in vivo , thereby effectively attenuating subsequent inflammation ( 159 , 160 ). Although a growing number of researchers have achieved a substantial progress in the understanding of the cellular mechanisms underlying these findings, much still remains elusive due to the extremely complex relationship between the nervous and immune systems with the involvement of OECs.…”
Section: Immune Properties Of Oecsmentioning
confidence: 99%
“…The regenerative capacity of the adult mammalian spinal cord after injury is extremely limited, mainly due to multifaceted adverse factors in addition to inflammatory cell activation that together contribute to a non-permissive environment and minimal functional recovery ( 1 , 16 , 160 , 161 ). Neuroinflammation is part of the primary responses to injury and might be linked to the characteristics of innate immune cells and immunological molecules involved in the injury area ( 19 , 162 , 163 ).…”
Section: Immune Properties Of Oecsmentioning
confidence: 99%